Effect of Robusta Coffee Extract on Histopathological in Mice Testes Induced with Monosodium Glutamat - Plumeriastuti, Hani; Weliyani, Trima; Hamid, Iwan Sahrial; Hidanah, Sri; Prastiya, Ragil Angga; Wibawati, Prima Ayu (Universitas Airlangga, 2021)
Monosodium glutamate (MSG) is a sodium salt from glutamic acid which is currently very popular to be used as a food flavoring ingredient to stimulate appetite. Exessive consumption of MSG can disrupt the balance of antioxidants and ROS, and cause the negative effects of oxidative stress on testes. Coffee has high chlorogenic acid, function for antioxidants and reduce the negative effect on cell damage in the testes. This study aims to analyze the effect of robusta coffee extract on histological of mice testes induced with MSG. This study was completely randomized design (CRD), using 20 male mice for 5 treatment groups: K+ (MSG 0.12 mg and Vitamin C 6 mg), K- (MSG 0.12 mg and CMC Na 0.1 ml), P1 (MSG 0.12 mg and RCE 0.1 mg), P2 (MSG 0.12 mg and RCE 0.2 mg), and P3 (MSG 0.12 mg and RCE 0.4 mg) orally for 42 days. Histophatological scores were analyzed with Saphiro-Wilk Test and Anova. There is no effect of increasing testicular weight. 0,12 mg MSG can cause a decrease in the number of spermatogonia and spermatocytes. 0,2 mg robusta coffee extract can maintain the number of spermatogonia and spermatocytes.